Empowering lifelong learning through micro-credentials in social security education - Awang Chek, Mohd Zaki; Ismail, Isma Liana (2025)
Financial literacy is a crucial component of effective financial decision-making, particularly concerning social security programs. In Malaysia, many individuals lack a comprehensive understanding of the various social security schemes, leading to inadequate financial planning, insufficient retirement funds, and underutilization of social security benefits. To address this issue, this study explores the integration of Micro-Credentials (MCs) as a transformative learning approach aimed at enhancing financial literacy through digital education. The UiTM uFuture platform serves as the foundation for delivering structured, competency-based courses that cater to diverse learners (https://ufuture.uitm.edu.my/courses/overview/UMC381). This innovation examines the implementation of MCs as an alternative to traditional financial education, emphasizing self-paced, modular, and interactive learning. The study employs a mixed-methods approach, including surveys, pre- and post-assessments, and participant feedback, to evaluate the effectiveness of MC-based learning. The pilot study involved 40 participants from diverse backgrounds, assessing their engagement levels, knowledge retention, and confidence in managing their financial security. The findings reveal that 87% of participants found the content highly engaging, while 88% reported increased confidence in making financial decisions regarding their social security benefits. The study underscores the potential of MCs in democratizing financial education by making learning more accessible, flexible, and engaging. By equipping individuals with essential financial knowledge and decision-making skills, this initiative supports the broader goal of fostering financial resilience and long-term economic stability. The adoption of MCs in social security education offers a scalable and sustainable approach to lifelong learning, ensuring continuous financial empowerment among Malaysians.